LEGAL PROTECTION OF TRADITIONAL DANCE ACCORDING TO INTERNATIONAL LAW - Aplia Eka Dewi (Faculty of Law Universitas Lampung, 2019)
Indonesia is a country that consists of various ethnics that have a diverse culture with the types and forms of art. One form of traditional art is a traditional dance that requires maintenance, preservation, and protection to be enjoyed by the next generation. Traditional dance is one of the cultural products that are also prone to become victims such as claims occur in Reog Dance and Pendet Dance by neighbouring countries. This research aims to determine the legal protection of traditional dance in International Law and the implementation of the legal protection of traditional dance in Indonesia.